Research of reserves of strengthening the income base of budgets of united territorial communities in decentralization conditions - Kvasnytsia, Oksana; Rusin, Viktor (Technology audit and production reserves, 2018)
The object of research is the theoretical and practical aspects of the formation of the revenue base of the budgets of the united territorial communities in the context of decentralization. One of the most problematic places of the object of research is the redistribution of powers and sources of formation of financial resources for their implementation between levels of the budget system. The process of decentralization is associated with the complexity and duration of the implementation of an effective system of providing the population with public services of an adequate level and quality. The work establishes the number of communities voluntarily united and what area of the territory and population of Ukraine is covered. The analysis of the current state of the formation of the revenue base of the budgets of the united territorial communities in the context of the implementation of the decentralization reform is carried out. In the process of research, general scientific and special research methods were used in their interrelation and interaction. In particular, abstract-logical techniques allow to find out what caused the problems arising in the process of forming the revenue base of the budgets of the united territorial communities. Among them there is a lack of professional staff in territorial communities and inadequate organization of cooperation between the executive bodies of companies and other participants in the budget process. The directions of strengthening the revenue base of the budgets of the united territorial communities are determined, which envisage measures: on unshadowing the incomes of employees and developing entrepreneurship in the community, will provide an opportunity to increase revenues to the budget from paying personal income tax; aimed at improving the administration of local taxes and fees, in particular, on setting rates and benefits; aimed at the legalization of excisable goods by retail entities; on the effective use of the property of the company; aimed at expanding the list of administrative services. Due to this, local governments of the united territorial communities will receive more resources in their budgets, which they can use to create comfortable living conditions in society.